Issues and Barriers to Social-Emotional Development in Early Childhood - Naimatul Ulfia Rahma; Zusy Aryanti; Dwi Enggal Wahyuni (Journal of Contemporary Pedagogy and Learning Science, 2026)
Social-emotional development is a crucial aspect of early childhood development as it influences children’s ability to regulate emotions, interact with others, and adapt to various social situations. However, many young children experience socio-emotional problems and developmental barriers that may affect their future growth and well-being. This study aims to identify and analyze the problems and barriers to social-emotional development in early childhood based on findings from previous studies. The research employed a qualitative library research method through a systematic review of relevant scientific articles on early childhood socio-emotional development. The findings indicate that common socio-emotional problems include poor emotional regulation, difficulties in peer interaction, social anxiety, aggressive behavior, social withdrawal, low self-confidence, and limited abilities in cooperation and empathy. These barriers are influenced by multiple factors such as inappropriate parenting styles, unsupportive social environments, negative peer experiences, excessive gadget use, and insufficient socio-emotional stimulation. The study concludes that emotional regulation is a central factor in determining children’s socio-emotional development outcomes. Therefore, active involvement from families, schools, and the wider community is essential to provide appropriate support and stimulation to optimize early childhood socio-emotional development.